Nanotechnology Driven Approach with Collagen and Mupirocin-loaded Silver Nanoparticles in Chitosan Hydrogel for Burn Wound Infection - Sankar, Veintramuthu (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The present investigation was to formulate Mupirocin- and collagen-loaded silver nanoparticles in chitosan hydrogel which has synergistic wound healing and anti-bacterial activity. Materials and Methods: Extraction and characterization of acid-soluble collagen from tilapia fish scales were performed. Mupirocin and collagen silver nanoparticles (Mup-AgNP-Col) were synthesized by chemical reduction method using sodium borohydride as reducing agent. Using design expert software, Mup-AgNP-Col preparations were optimized. Chitosan hydrogel was prepared and the optimized Mup-AgNP-Col formulation was loaded in the gel and evaluation parameters were assessed. Results: The optimized Mup-AgNP-Col formulation with silver nitrate concentrations of 4.3 mM, sodium borohydride concentration of 2 mM, and collagen concentration of 0.1 mg showed spherical structure with particle size as 121 ± 1.18 nm. The entrapment efficiency was found to be 91.3 ± 2.8 % and at the end of 6 h in vitro, release studies showed 91 ± 2.89% drug release in phosphate buffer, pH 7.4. Non-toxic and wound-healing activity was confirmed by L929 fibroblast cell line study. The formulated gel was evaluated for its spreadability and extrudability. Conclusion: Mup-AgNP-Col in chitosan hydrogel enhances burn wound healing.